Project onward: an innovative e‐health intervention for cancer survivors. Issue 4 (21st March 2012) - Duffecy, Jennifer; Sanford, Stacy; Wagner, Lynne; Begale, Mark; Nawacki, Ewa; Mohr, David C.
Abstract Objective This study examined the feasibility and acceptability of an Individual Internet Intervention (III) embedded and integrated into an Internet Support Group (ISG) with the ultimate goal of enhancing adherence and learning, compared with an individual internet invention alone. Method Thirty‐one posttreatment cancer survivors were randomized in groups of seven to nine to either the 8‐week III + ISG intervention or the 8‐week III condition. Seventeen participants met the Hospital Anxiety and Depression Scale (HADS) criteria for depressive symptoms (HADS ≥ 8). Results Among all participants, the mean number of logins over 8 weeks was 20.8 ± 17.7 logins for the III + ISG compared with 12.5 ± 12.5 in III‐only (p = 0.15). Two participants in the III + ISG dropped out, compared with five in III (p = 0.39). Among the 17 participants with depressive symptoms at baseline, both the Onward and the III‐only condition showed large reductions in the depression scale of HADS (d = 1.27 and 0.89, respectively). Improvement over time and time x treatment effects only reached trend significance levels (ps = 0.07 & 0.12) as this pilot was not powered to detect these differences. Conclusion Both the III + ISG and III‐only demonstrated pre‐post reductions in depressive symptoms and high rates of utilization compared with other web‐based treatments for depression. Although it is premature to make any determination as to the efficacy of the interventions tested in this feasibility study, these results indicate that pursuing the III + ISG model, as well as standard IIIs, may be fruitful areas of future research. Copyright © 2012 John Wiley & Sons, Ltd.